PENGARUH AUDIT FEE, AUDIT TENURE, ROTASI AUDIT DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP KUALITAS AUDIT: THE EFFECT OF AUDIT FEE, AUDIT TENURE, AUDIT ROTATION AND THE REPUTATION OF PUBLIC ACCOUNTING FIRM ON AUDIT QUALITY - Ibnu Fadhlan; Yuneita Anisma; Sem Paulus Silalahi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
The purpose of this study was to analyze the influence of audit fees, tenure, rotation, and accounting public firms’ reputations on audit quality. Audit quality is the ability of the auditor to detect irregularities or errors in financial statements and report them to users of who use the financial statements. The population in this study are all transportation sub-sector companies listed on the IndonesiaiStock Exchange (IDX) in 2016-2020. Purposive sampling was utilized to choose the study's sample. Twelve businesses were chosen as the sample in this study using pre-established criteria.The data analysis method used is multiple linear regression. The results of the study show that the audit fee and the reputation of the public accounting firm have an effect on audit quality. Meanwhile, audit tenure and audit rotation have no effect on audit quality